Vibrio vulnificus—A Review with a Special Focus on Sepsis - Marcello Candelli; Marta Sacco Fernandez; Cristina Triunfo; Andrea Piccioni; Veronica Ojetti; Francesco Franceschi; Giulia Pignataro (Microorganisms)
Vibrio vulnificus (V. vulnificus) is a Gram-negative, halophilic bacillus known for causing severe infections such as gastroenteritis, necrotizing fasciitis, and septic shock, with mortality rates exceeding 50% in high-risk individuals. Transmission occurs primarily through the consumption of contaminated seafood, exposure of open wounds to infected water, or, in rare cases, insect bites. The bacterium thrives in warm, brackish waters with high salinity levels, and its prevalence is rising due to the effects of climate change, including warming ocean temperatures and expanding coastal habitats. High-risk populations include individuals with underlying conditions such as chronic liver disease, diabetes, or immunosuppression, which heighten susceptibility to severe outcomes. The pathogenicity of V. vulnificus is mediated by an array of virulence factors, including hemolysins, proteases, and capsular polysaccharides, as well as mechanisms facilitating iron acquisition and immune system evasion. Clinical manifestations range from localized gastrointestinal symptoms to life-threatening systemic infections such as septicemia. Rare but severe complications, including pneumonia and meningitis, have also been reported. Treatment typically involves the use of doxycycline in combination with third-generation cephalosporins, although the emergence of multidrug-resistant strains is an escalating concern. Alternative therapeutic approaches under investigation include natural compounds such as resveratrol and the application of antimicrobial blue light. For necrotizing infections, prompt and aggressive surgical intervention remains essential to improving patient outcomes. As global temperatures continue to rise, understanding the epidemiology of V. vulnificus and developing innovative therapeutic strategies are critical to mitigating its growing public health impact.